Board gender diversity and firm performance: Evidence from the Russian agri-food industry - Alisher Tleubayev; Ihtiyor Bobojonov; Taras Gagalyuk; Thomas Glauben (International Food and Agribusiness Management Review, 2020)
This study provides pioneering empirical evidence on board gender diversity and firm performance relationship for the case of large-scale agri-food companies in Russia. While Russia plays an important role in the global food security, its domestic agri-food production is heavily dependent on large scale producers. Our findings suggest a strong positive link between the percentage of female directors in boardrooms and firm performance. Moreover, in line with critical mass theory, boards with three or more female directors have greater impact on firm performance compared to boards with two or less female directors. Further analysis shows that the presence of female directors in the company has a positive impact on firm performance, mainly due to their executive, rather than monitoring effects. The paper shed light on gender diversity of Russian corporate boardrooms and provides empirical recommendations for policy makers as well as corporate executives in Russia.
Keywords: M14; Q12; Q13; 650; corporate governance; board of directors; gender diversity; firm performance; Russia